2022
DOI: 10.3389/fbioe.2022.959842
|View full text |Cite
|
Sign up to set email alerts
|

Design feature combinations effects of running shoe on plantar pressure during heel landing: A finite element analysis with Taguchi optimization approach

Abstract: Large and repeated impacts on the heel during running are among the primary reasons behind runners’ injuries. Reducing plantar pressure can be conducive to reducing running injury and improving running performance and is primarily achieved by modifying the design parameters of running shoes. This study examines the effect of design parameters of running shoes (i.e., heel-cup, insole material, midsole material, and insole thickness) on landing peak plantar pressure and determines the combination of different pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…It has been shown that high archers have a reduced calcaneal pitch when standing in semi-customized insoles with arch support ( Eslami et al, 2009 ). In addition, the heel cup design reduces impact and increases ankle stability during running ( Manoli and Graham, 2005 ; Yang et al, 2022 ). These findings suggest that personalized orthotic insoles are effective in distributing plantar pressure during running in patients with SCF.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that high archers have a reduced calcaneal pitch when standing in semi-customized insoles with arch support ( Eslami et al, 2009 ). In addition, the heel cup design reduces impact and increases ankle stability during running ( Manoli and Graham, 2005 ; Yang et al, 2022 ). These findings suggest that personalized orthotic insoles are effective in distributing plantar pressure during running in patients with SCF.…”
Section: Discussionmentioning
confidence: 99%
“…Cushioning insoles should provide adequate cushioning while creating a safe and stable mechanical environment for the lower extremities ( Withnall et al, 2006 ). They should rapidly absorb energy and sustain low deformation when the lower extremities are subjected to large impacts ( Yang et al, 2022 ). This study used a gravity-driven impact test to quantify the energy absorption and deformation levels of three types of ACF and EVA materials.…”
Section: Discussionmentioning
confidence: 99%
“…They evaluated the viscoelastic properties between new and used shoes to assess their effectiveness over time. Yang et al [88] investigated parameters crucial for optimal sports shoe design and reducing plantar pressure. They applied the Taguchi method to determine the best combination of these parameters and validated the model using Ansys TM .…”
Section: Other Control Methodsmentioning
confidence: 99%